The Northern European Renaissance / Teacher's Guide; 12 Coloured Overhead Transparencies and 12 Spiritmaster Pages - Chase Marilyn; Holmes Mcdougall (1981)
Humanists of Northern Europe, Johann Gutenberg, Martin Luther, Martin Luther's Beliefs and Accomplishments, Elizabeth I and Renaissance Queen, Elizabethan English, Elizabethan England, Elizabethan Drama, Poor People of the Renaissance, Chateaux of France, Elegant Dining of the Renaissance, Science and Scientists of Northern Europe.